Nonaligned modernism : socialist postcolonial aesthetics in Yugoslavia, 1945-1985 - Videkanić, Bojana, 1977- (McGill-Queen's University Press, 2019)
"In less than half a century, the Socialist Federal Republic of Yugoslavia successfully defeated Fascist occupation, fended off dominating pressures from the Eastern and Western blocs, built a modern society on the ashes of war, created its own form of socialism, and led the formation of the Nonaligned Movement. This country's principles and its continued battles, fought against all odds, provided the basis for dynamic and exceptional forms of art. Drawing on archival materials, postcolonial theory, and Eastern European socialist studies, Nonaligned Modernism chronicles the emergence of late modernist artistic practices in Yugoslavia from the end of the Second World War to the mid-1980s. Situating Yugoslav modernism within postcolonial artistic movements of the twentieth century, Bojana Videkanić explores how cultural workers collaborated with others from the Global South to create alternative artistic and cultural networks that countered Western hegemony. Videkanić focuses primarily on art exhibitions along with examples of international cultural exchange to demonstrate that nonaligned art wove together politics and aesthetics, and indigenous, Western, and global influences. An interdisciplinary book, Nonaligned Modernism highlights Yugoslavia's key role in the creation of a global modernist ethos and international postcolonial culture."--